2018
DOI: 10.1093/mutage/gex045
|View full text |Cite
|
Sign up to set email alerts
|

Chronic occupational exposure endured by tobacco farmers from Brazil and association with DNA damage

Abstract: Tobacco farming is an important economic income in Brazil, although it has been challenged as regard the occupational exposure to both pesticides and nicotine endured by farmers. Chronic occupational exposure to complex mixtures can lead to health hazardous. We examined genomic instability and epigenetic changes in tobacco farmers occupationally exposed to pesticide mixtures and nicotine at tobacco fields. DNA damage was assessed by alkaline comet assay in blood cells. Genomic DNA was isolated, and telomere le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 58 publications
1
6
0
7
Order By: Relevance
“…The main form of pesticide application reported by the study volunteers was the costal pump, which is cited by several authors as an additional factor of exposure, followed by application using tractors without a booth, which is mistakenly treated as safe by volunteers using majority, only ear protectors during application using this vehicle. These results are consistent with other studies carried out in other regions of Brazil, showing a great use of this pesticide and the absence of care at the time of use (Cattelan et al, 2018;Kahl et al, 2018;Santos et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…The main form of pesticide application reported by the study volunteers was the costal pump, which is cited by several authors as an additional factor of exposure, followed by application using tractors without a booth, which is mistakenly treated as safe by volunteers using majority, only ear protectors during application using this vehicle. These results are consistent with other studies carried out in other regions of Brazil, showing a great use of this pesticide and the absence of care at the time of use (Cattelan et al, 2018;Kahl et al, 2018;Santos et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a consortium called Agricultural Health Study (AHS) has approached the influence of exposure to pesticides in crop farms to telomere length, although those studies are not clear which pesticides, whether as pure or mixture use, and which crop are being investigated [ 44 , 45 ]. Our group demonstrated shorter telomere length in tobacco farmers, exposed to both pesticides and nicotine from tobacco leaves, is associated with increased oxidative stress levels and trace and ultratrace element status [ 17 , 46 ]. Along with the available data in literature, the influence of pesticides on telomere length demonstrates that occupational exposure to pesticides presents a long-term effect on farmers [ 7 , 11 , 13 , 21 , 30 , 31 , 42 , 44 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Ni carcinogenic potential relates to its ability to accelerate epigenetic changes including DNA methylation. On a former study from our group, the shorter TL in tobacco farmers was related to hypermethylation of the p16 gene [ 46 ]. Nickel was found to promote gene-specific hypermethylation of the tumor suppressor p16 in several studies (reviewed by [ 70 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Ttest evaluated the statistical significance of a feature's differential values between two groups of samples (Kim, 2015;Gharbali et al, 2018;Jankowski et al, 2018). This study focused on the differential methylated residues between the RA patients and the siblings and assumed the independences between the two groups of samples (Lotsch et al, 2013;Kahl et al, 2018).…”
Section: Filter Algorithmsmentioning
confidence: 99%